Impact of supplementation with milk–cereal mix during 6–12 months of age on growth at 12 months: a 3-arm randomized controlled trial in Delhi, India. Issue 1 (12th October 2021) - Taneja, Sunita; Upadhyay, Ravi P; Chowdhury, Ranadip; Kurpad, Anura V; Bhardwaj, Himani; Kumar, Tivendra; Dwarkanath, Pratibha; Bose, Beena; Devi, Sarita; Kumar, Gunjan; Kaur, Baljeet; Bahl, Rajiv; et al.
ABSTRACT: Background: A large proportion of infants in low- and middle-income countries are stunted. These infants are often fed complementary foods that are low-quality, primarily in terms of protein and micronutrients. Objectives: We aimed to test 2 milk–cereal mixes supplemented with modest and high amounts of protein during 6–12 mo of age, compared with no supplementation, for their effect on length-for-age z score (LAZ) at 12 mo of age. Methods: Eligible infants (6 mo plus ≤29 d) were randomly assigned to either of the 2 interventions (modest- and high-protein) or a no supplement group. The milk–cereal mixes provided ∼125 kcal, 30%–45% energy from fats, and 80%–100% RDA of multiple micronutrients (MMN). The modest-protein group received 2.5 g protein [protein energy ratio (PER): 8%; 0.75 g from milk source] and the high-protein group received 5.6 g protein (PER: 18%, 1.68 g from milk source). One packet was given daily for 180 d. Counseling on continued breastfeeding and optimal infant-care practices was provided to all. Results: We enrolled 1548 infants (high-protein: n  = 512; modest-protein: n  = 519; and no supplement: n  = 517). Compared with the no supplement group, there was an improvement in LAZ [adjusted mean difference (MD): 0.08; 95% CI: 0.01, 0.15], weight-for-age z score (MD: 0.12; 95% CI: 0.06, 0.19), weight-for-length z score (MD: 0.11; 95% CI: 0.02, 0.19), and midupper arm circumference z score (MD: 0.10; 95% CI: 0.02, 0.18) in the high-protein group at 12 mo of age. No significant differences for these anthropometric indicators were noted between the modest-protein and no supplement groups or between the high- and modest-protein groups. Conclusions: Cereal mixes with higher amounts of milk-based protein and MMN may lead to improvement in linear growth and other anthropometric indexes in infants, compared with no supplementation. This trial was registered at ctri.nic.in as CTRI/2018/04/012932.